Non-POEMS osteosclerotic multiple myeloma: Clinical characteristics and differential diagnosis - Li, Zi-Yan; Chen, Jiang-Jie; Lu, Fang-Ying; Gan, Mei-Fu; Tung, Tao-Hsin; Hong, Dun (Journal of bone oncology, 2024)
•Rare non-POEMS osteosclerotic MM case presented and terminology standardized.•Review since 1990 identifies just 12 non-POEMS osteosclerotic MM cases.•The disease is divided into osteosclerotic lesion and diffuse osteosclerosis subtypes.•Polyneuropathy and organomegaly distinguish POEMS from non-POEMS MM.•Hyperactive osteoblastic process may underlie the etiology. Osteosclerosis in multiple myeloma (MM) is typically associated with rare POEMS syndrome, characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), M-protein (M), and skin changes (S). However, osteosclerosis in multiple myeloma (MM) without POEMS syndrome, defined as non-POEMS Osteosclerotic MM, is exceedingly rare. We report a 70-year-old man with rib pain, remarkably high bone mineral density and diffuse osteosclerosis. The diagnosis of non-POEMS osteosclerotic MM was confirmed by biopsy and aspiration of bone marrow through surgery. A literature review spanning from 1990 identified 12 cases of similar non-POEMS osteosclerotic MM, including 5 males and 7 females with a mean age of 59.7 ± 10.6 years. The non-POEMS osteosclerotic MM can be divided into two subtypes, the osteosclerotic lesion subtype and the diffuse osteosclerosis subtype. Absence of polyneuropathy and organomegaly are the main factors that differentiate non-POEMS osteosclerotic MM from POEMS. A hyperactive osteoblastic process might be the etiology of diffuse osteosclerosis. Further research is needed to understand its etiology and pathophysiology.